Maternal Hypercholesterolemia Associated with Nicotine Exposure in Adulthood May Induce Kidney Injury in Male Rats if Hypomagnesemia Occurs - Claudia M.B. Helou; Rildo A. Volpini; Mirela A.R. Santinho; Fabricio L. Fonseca; André L. Simião (Karger Publishers, 2017)
Background/Aims: Maternal hypercholesterolemia is a risk factor to renal injury in rat pups at adulthood, especially if they feed a cholesterol-enriched diet after weaning. However, the renal function of male pups of dams with hypercholesterolemia (PH) that were fed a regular chow from weaning to adulthood needs investigation, particularly those exposed to an adverse risk such as nicotine. Methods: We evaluated the renal function of PH animals and we compared the data with those found in male pups of control dams (PC) at 3- and 6-month-old by inulin clearance. Moreover, we investigated the effect of nicotine treatment for 8 days in both PH and PC animals at 6 months old via metabolic function studies and by renal histological analysis. Results: Inulin clearance and other renal function parameters were similar in PH and PC animals at 3 and 6 months old. Nevertheless, the PH group showed significant differences with regard to histological analysis despite a similar number of glomeruli. The glomerular area of PH animals was significantly smaller than that measured in PC animals, and the fractional interstitial area was significantly larger in PH animals than that measured in PC animals at 3 months old. With regard to nicotine treatment, we observed a trend for a reduction in creatinine clearance in both PC and PH groups, but only PH animals showed hypomagnesemia and the highest fractional interstitial area. Conclusions: The offspring exposed to a high cholesterol milieu during intrauterine and neonatal life may show a silent kidney injury at adulthood that may be aggravated by nicotine exposure if hypomagnesemia occurs.